Event-by-event correlations between Λ ( ¯¯¯ Λ ) hyperon global polarization and handedness with charged hadron azimuthal separation in Au + Au collisions at √ s N N = 27 GeV from STAR - STAR Collaboration (Physical Review C, 2023)
Global polarizations (P) of Λ (¯¯¯Λ) hyperons have been observed in noncentral heavy-ion collisions. The strong magnetic field primarily created by the spectator protons in such collisions would split the Λ and ¯¯¯Λ global polarizations (ΔP=PΛ−P¯¯¯Λ<0). Additionally, quantum chromodynamics predicts topological charge fluctuations in vacuum, resulting in a chirality imbalance or parity violation in a local domain. This would give rise to an imbalance (Δn=NL−NR⟨NL+NR⟩≠0) between left- and right-handed Λ (¯¯¯Λ) as well as a charge separation along the magnetic field, referred to as the chiral magnetic effect (CME). This charge separation can be characterized by the parity-even azimuthal correlator (Δγ) and parity-odd azimuthal harmonic observable (Δa1). Measurements of ΔP, Δγ, and Δa1 have not led to definitive conclusions concerning the CME or the magnetic field, and Δn has not been measured previously. Correlations among these observables may reveal new insights. This paper reports measurements of correlation between Δn and Δa1, which is sensitive to chirality fluctuations, and correlation between ΔP and Δγ sensitive to magnetic field in Au+Au collisions at 27 GeV. For both measurements, no correlations have been observed beyond statistical fluctuations.
0 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed